2020
DOI: 10.1016/j.molmet.2020.101104
|View full text |Cite
|
Sign up to set email alerts
|

Female mice exposed to low doses of dioxin during pregnancy and lactation have increased susceptibility to diet-induced obesity and diabetes

Abstract: Objective Exposure to persistent organic pollutants is consistently associated with increased diabetes risk in humans. We investigated the short- and long-term impact of transient low-dose dioxin (2,3,7,8-tetrachlorodibenzo- p -dioxin, TCDD) exposure during pregnancy and lactation on glucose homeostasis and beta cell function in female mice, including their response to a metabolic stressor later in life. Methods Female mice were injected with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(62 citation statements)
references
References 46 publications
(53 reference statements)
10
33
0
Order By: Relevance
“…Furthermore, HFD feeding induced hyperinsulinemia in CO-exposed female mice and both TCDD-and CO-exposed male mice, but failed to induce compensatory hyperinsulinemia in TCDD-exposed females. These findings are in line with our previous work showing that female mice exposed to low-dose TCDD during pregnancy/lactation and subsequently fed HFD later in life had accelerated onset of hyperglycemia and transient low glucose-induced plasma insulin levels compared to COHFD females (22). Furthermore, RNA-Seq analysis on isolated islets revealed that TCDD exposure promoted abnormal changes to endocrine and metabolic pathways in HFD-fed females.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, HFD feeding induced hyperinsulinemia in CO-exposed female mice and both TCDD-and CO-exposed male mice, but failed to induce compensatory hyperinsulinemia in TCDD-exposed females. These findings are in line with our previous work showing that female mice exposed to low-dose TCDD during pregnancy/lactation and subsequently fed HFD later in life had accelerated onset of hyperglycemia and transient low glucose-induced plasma insulin levels compared to COHFD females (22). Furthermore, RNA-Seq analysis on isolated islets revealed that TCDD exposure promoted abnormal changes to endocrine and metabolic pathways in HFD-fed females.…”
Section: Discussionsupporting
confidence: 91%
“…Further, the compensatory increase in Nkx6.1 in COHFD females compared to COChow was absent in TCDDHFD females. These findings are consistent with our pregnancy model showing a reduced proportion of beta cells expressing MAFA in the pancreas of TCDDHFD females compared to COHFD females (22). The beta cell transcription factors MAFA, PDX1, HNF4α, and PAX6 form an essential network for maintaining beta cell identity and regulating genes involved in insulin secretion (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations